PENGARUH PROFESIONALISME DAN MOTIVASI KERJA TERHADAP KINERJA KARYAWAN PADA PT BPD JATIM (Studi Pada Kantor Cabang Surabaya) - UNGGULLAGA, IBRAHIM (Jurnal Ilmu Manajemen (JIM), 2017)
PT BPD JATIM is one of the biggest bank in East Java who want to always improve services to customers. The purpose of this study is to determine the effect of professionalism and work motivation on employee performance. The sample used in this research is 31 employees of operational division by using saturated sampling method. This study uses a quantitative approach that uses primary data obtained by using questionnaires. Methods of multiple linear regression analysis is the analysis used in this study. The results of this study indicate the existence of profeionalisme not significant to employee performance and work motivation has a significant effect on employee performance. The recommended recommendations from the results of this study are companies that need to improve professionalism again in a way that more conducts training to employees, and employee motivation assessment needed is certainly good enough for the company. Key words: professionalisme, work motivation, employee performance